Media bias in women's magazines: Do advertisements influence editorial content? - Julia Pannicke (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2015)
Existing theoretical and empirical studies on Media Bias are subjects of controversial discussions in the literature. However, scientific literatures on Media Bias establish empirical evidence for a positive impact of advertising volume on media coverage. To get in line with the debated literature about whether biases occur, this economic paper presents an empirical analysis of a possible (commercial) Media Bias influenced by advertising expenditure in monthly womens magazines. The results of a linear panel model regression, a panel poisson regression, as well as those of a panel negative binomial regression model show that there is a positive correlation with the amount of advertising expenditure on the coverage of a company that purchased advertisements on the women's magazines in Germany. A positive correlation between advertising volume and the nomination as well as prize winning of (cosmetic) products could also be found.
Keywords: 330; media bias; advertisement; advertising volume; coverage; two-sided markets